Internalization of Islamic Economic Law in Facing the Challenges of Shopee’s Digitalization - Nur Aefih; Zainal Said; Hannani Yunus (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2026)
The development of digital technology has driven significant changes in the economic transaction system of society, particularly through the use of digital platforms such as Shopee. These changes have brought various conveniences to trading activities, but also raise new challenges in terms of legal regulation, consumer protection, and the application of Islamic economic law principles. This study aims to analyze the concept of Islamic economic law in digital transactions, examine regulatory challenges in the digital era, and formulate a reconstruction model of Islamic economic law oriented towards the paradigm of justice in transactions on digital platforms. This study uses a normative legal research method with a conceptual and legislative approach, supported by a literature review of various legal sources and relevant literature. The results show that the principles of Islamic economic law, such as justice (al-’adl), transparency, and benefit (maslahah), remain relevant in regulating digital transactions, but require regulatory reconstruction that is adaptive to technological developments. This reconstruction of Islamic economic law is necessary through strengthening digital contracts, platform responsibility, consumer protection, and the integration of the maqasid al-shariah principle in regulatory development. Thus, the reconstruction of Islamic economic law is expected to be able to create a digital transaction system that is fair, transparent, and oriented towards the welfare of society in the modern digital economic era.